Emergence of Mycoplasma genitalium with clinically significant fluoroquinolone resistance conferred by amino acid changes both in GyrA and ParC in Japan. Issue 9 (September 2017) - Deguchi, Takashi; Ito, Shin; Yasuda, Mitsuru; Kondo, Hiromi; Yamada, Yoshiteru; Nakane, Keita; Mizutani, Kosuke; Tsuchiya, Tomohiro; Yokoi, Shigeaki; Nakano, Masahiro
Abstract: We observed fluoroquinolone treatment failures in 2 men with Mycoplasma genitalium -positive non-gonococcal urethritis in Japan. A fluoroquinolone regimen of sitafloxacin 100 mg twice daily for 7 days failed to eradicate M. genitalium . In both cases, M. genitalium had fluoroquinolone resistance-associated amino acid changes both in GyrA and ParC and a macrolide resistance-associated mutation in the 23S rRNA gene. The emergence of such multi-drug resistant strains can threaten antimicrobial chemotherapy for M. genitalium infections in Japan, because we will lose the first- (azithromycin) and second-line (sitafloxacin) antimicrobial agents to treat M. genitalium infections. We prescribed an extended minocycline regimen of minocycline 100 mg twice daily for 14 days for our patients, and the regimen was successful in eradicating the M. genitalium . The extended minocycline regimen might be an option that we can try when treating multi-drug resistant M. genitalium infections in clinical practice.